A comprehensive overview and safety evaluation of fremanezumab as a preventive therapy for migraine. Issue 5 (3rd May 2020) - Parikh, Simy K.; Burkett, John G.; Silberstein, Stephen D.
ABSTRACT: Introduction : Fremanezumab, a humanized monoclonal antibody targeting calcitonin gene-related peptide (CGRP mAb), is a migraine-specific treatment for migraine prevention. Areas covered : This review will briefly discuss other available and emerging CGRP mAbs and the neurophysiology of fremanezumab. The review will focus on phase III trials of the efficacy of fremanezumab for episodic and chronic migraine, and a recent pooled safety and tolerability analysis of its use. Expert opinion : Continued efficacy and safety data collection will help guide long-term risk and efficacy counseling in the general population.